HIV/AIDS awareness and risk behavior among students in Semey, Kazakhstan: a cross-sectional survey - Ahlm Clas; Urazalin Marat; Stockfelt Leo; Hansson Marit; Andersson Rune (BMC, 2008)
Abstract Background Until recently, young people in Kazakhstan have been only moderately affected by the global HIV epidemic. Today, however, the HIV epidemic in Central Asia is one of the most rapidly increasing epidemics in the world. It is mainly concentrated to vulnerable groups such as intravenous drug users, sex workers, the purchasers of sexual services and the financially marginalized. Young, sexually active people may however be the gateway for the epidemic to the general population, and knowledge about their attitudes and behavior is therefore important in planning preventive measures. Methods To gather information about young students and their attitudes and knowledge about HIV/AIDS, we collected 600 structured questionnaires and made 23 semi-structured interviews among three groups of students. Response rate was 99%. Results Almost 99% of the respondents had heard of HIV/AIDS, and 89% could identify ways to protect oneself against sexually transmitted HIV/AIDS. The main routes of transmission, sexual contact without condom and intravenous drug use, were both identified by 97% of the students. Twenty-five percent of the female students and 75% of the male students had had one or more sexual partners. More than 30% of the young men had purchased sex, and homosexuality was widely stigmatized. Conclusion Risks for the spread of HIV/AIDS among young people in Kazakhstan include prostitution as well as stigmatization of the HIV positive and of homosexuals. Protective factors are good knowledge about risks and protection, and opportunities to talk and gather information about sexuality and HIV/AIDS.